2015
DOI: 10.1016/j.astropartphys.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Dipole anisotropy in sky brightness and source count distribution in radio NVSS data

Abstract: We study the dipole anisotropy in number counts and flux density weighted number counts or sky brightness in the NRAO VLA Sky Survey (NVSS) data. The dipole anisotropy is expected due to our local motion with respect to the CMBR rest frame. We analyse data with an improved fit to the number density, n(S), as a function of the flux density S, which allows deviation from a pure power law behaviour. We also impose more stringent cuts to remove the contribution due to clustering dipole. In agreement with earlier r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 39 publications
9
102
0
Order By: Relevance
“…The CMB dipole was measured with high accuracy by the Planck collaboration (Akrami et al 2018): v = 369.82 ± 0.11 km/s towards (264.021 ± 0.011 , 48.253 ± 0.005) • , Measurements performed using these and other radio continuum catalogues have found that the radio dipole is compatible with the CMB dipole direction, but the dipole amplitude is 2 − 5 times larger than the signal observed in the CMB (Blake & Wall 2002;Singal 2011;Gibelyou & Huterer 2012;Rubart & Schwarz 2013;Tiwari et al 2014;Tiwari & Jain 2015;Tiwari & Nusser 2016;Colin et al 2017;Bengaly et al 2018b). However, no significant evidence for anomalous anisotropy in galaxy counts was reported at lower redshift ranges, such as those probed by visible and infrared catalogues (Itoh et al 2010;Gibelyou & Huterer 2012;Yoon et al 2014;Alonso et al 2015a;Yoon & Huterer 2015;Javanmardi & Kroupa 2017;Bengaly et al 2017Bengaly et al , 2018aRameez et al 2018).…”
Section: Introductionmentioning
confidence: 95%
“…The CMB dipole was measured with high accuracy by the Planck collaboration (Akrami et al 2018): v = 369.82 ± 0.11 km/s towards (264.021 ± 0.011 , 48.253 ± 0.005) • , Measurements performed using these and other radio continuum catalogues have found that the radio dipole is compatible with the CMB dipole direction, but the dipole amplitude is 2 − 5 times larger than the signal observed in the CMB (Blake & Wall 2002;Singal 2011;Gibelyou & Huterer 2012;Rubart & Schwarz 2013;Tiwari et al 2014;Tiwari & Jain 2015;Tiwari & Nusser 2016;Colin et al 2017;Bengaly et al 2018b). However, no significant evidence for anomalous anisotropy in galaxy counts was reported at lower redshift ranges, such as those probed by visible and infrared catalogues (Itoh et al 2010;Gibelyou & Huterer 2012;Yoon et al 2014;Alonso et al 2015a;Yoon & Huterer 2015;Javanmardi & Kroupa 2017;Bengaly et al 2017Bengaly et al , 2018aRameez et al 2018).…”
Section: Introductionmentioning
confidence: 95%
“…If this rest frame is the same as the CMB rest frame, then the dipole measured in the radio catalogue should agree with the CMB dipole measured by WMAP and Planck (Jarosik et al 2011;Planck Collaboration XXVII 2014). Previous studies 6 (Blake & Wall 2002a;Singal 2011;Gibelyou & Huterer 2012;Rubart & Schwarz 2013;Tiwari et al 2015;Singal 2014) measured the radio dipole for the NVSS catalogue. It is actually significantly larger than expected, by a factor of two to four depending on the details of the analysis.…”
Section: Dipole Correctionmentioning
confidence: 99%
“…It has been tried to explain this preferred direction as a result of the peculiar motion of the solar system [10,11]. But the peculiar velocities determined from CMBR data and from radio data are not consistent with each other [11][12][13]. This suggests the existence of an intrinsic anisotropy in the large scale with the anisotropy axis roughly aligned along the CMBR dipole [12].…”
Section: Introductionmentioning
confidence: 83%
“…But the peculiar velocities determined from CMBR data and from radio data are not consistent with each other [11][12][13]. This suggests the existence of an intrinsic anisotropy in the large scale with the anisotropy axis roughly aligned along the CMBR dipole [12]. In recent years, single mode super-horizon perturbations have been considered [14,15] to explain the observed dipolar anisotropy as the wavevector corresponding to a single mode can readily introduce a special direction in the universe.…”
Section: Introductionmentioning
confidence: 91%